A80 ADVANCED ENDOSCOPIC RESECTION OF LARGE POLYPS & EARLY NEOPLASIA: OUTCOMES OF ENDOSCOPIC MUCOSAL RESECTION IN BRITISH COLUMBIA - Zhao, B (J Can Assoc Gastroenterol, 2020)
BACKGROUND: Recent advances have resulted in a new technique termed endoscopic mucosal resection (EMR). This procedure has been successful at removing large or complex polyps and achieving remission rates comparable to surgery. EMR can also be used to remove early, non-metastatic cancer and they are less invasive than surgery. However, they have been associated with their own complications, most serious of which being perforation. This procedure has recently become available in British Columbia for resection of both complex polyps and early established cancers in the colon. AIMS: Here we present patient outcomes of EMR procedures for the resection of colorectal polyps in British Columbia. METHODS: Retrospective data were collected on all EMR procedures done in Vancouver General Hospital and St. Paul’s Hospital (Vancouver, B.C.) from October 2012 (when procedure became available) to July 2019. Inclusion criteria were all adults who had undergone EMR for resection of polyps in the colon. Exclusion criteria were patients younger than 18 or patients who had EMR that resected polyps in the upper GI tract. Patients were referred to one of two endoscopists when one or more polyps suitable for EMR were identified during colonoscopy by other gastroenterologists. Collected data included patient demographics, polyp characteristics, procedure outcome, and complications. RESULTS: There were 211 EMR procedures performed on 182 patients (48.9% male). Patient age ranged from 27 to 86 (mean = 67.1). A total of 244 colon polyps were removed with an average size of 2.91 cm and ranged from 0.8 cm to 15 cm. Resected polyps had the following distribution: ascending colon (63.5%), transverse colon (10.2%), descending colon (5.7%), sigmoid colon (15.2%), and rectum (5.3%). Of those that reported resection type, 84.2% were piecemeal and 15.8% were en bloc. 40.9% of polyps were tubulovillous adenoma, 33.2% were tubular, 16.2% were sessile serrated, 6.4% were villous, and 3.4% were adenocarcinoma. Patients from 11 of the 211 EMR cases (5.2%) experienced post-procedure bleed and 4 of these 11 patients (36.4%) had been on anti-platelet or anti-coagulants (discontinued before procedure). Overall, patients from 51 (24.2%) EMR cases were on anti-platelet or anti-coagulants. 33 cases (15.6%) had residual polyps at the resection site that required additional endoscopic resection during follow-up and 14 patients (6.6%) required surgery. None of the EMR procedures resulted in perforation. CONCLUSIONS: EMR is an effective minimally-invasive procedures that can be used to remove large, complicated colonic polyps and achieve long-term remission rate. The procedure has an acceptable risk profile, with complication and re-intervention rate similar or less than other procedures used to remove large, complicated polyps. FUNDING AGENCIES: None